Inquiry Learning to Improve Critical Thinking Skills and Student Learning Outcomes - Bonita Hirza; Luvi Antari; Rohman Rohman (STAI Hubbulwathan Duri, 2025)
Developing students' critical thinking skills and improving cognitive learning outcomes remain essential goals in mathematics education. This study aimed to examine the implementation and effectiveness of the Inquiry Learning model in enhancing students' critical thinking abilities and understanding of prism and pyramid concepts. This research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart (1988) spiral model, consisting of four stages: planning, acting, observing, and reflecting. The study was conducted in two cycles involving 27 students of class IX B at MTs Muqimus Sunnah Palembang. The learning process integrated inquiry-based instruction supported by Student Worksheets (LKPD). Findings indicated a significant improvement in students’ cognitive learning outcomes. By the end of the second cycle, 81.48% of students achieved the minimum mastery criteria, reflecting increased understanding of geometric concepts. Observational data also revealed enhanced student engagement and active participation. The Inquiry Learning model effectively promoted critical thinking through student-led problem exploration, hypothesis formulation, and data analysis. The success of the Inquiry Learning model was attributed to its student-centered approach, which encouraged active learning and deeper conceptual understanding. Students demonstrated improved reasoning and problem-solving skills as a result of engaging with real learning challenges. The application of the Inquiry Learning model, supported by structured worksheets, effectively improved both critical thinking skills and cognitive learning outcomes in geometry. This model is recommended for broader implementation in similar educational contexts.